Can corporate reputation complement or substitute underwriter reputation in seasoned equity offerings? - Ng, Xin Yin (2021)
Announcements of seasoned equity offerings (SEOs) in Hong Kong, including open offers and rights issues, tend to induce negative price reactions that are more severe than in the Western sphere. We hypothesise that corporate reputation can narrow the information asymmetry between issuers and investors to mitigate the negative price reaction. Our analyses show, however, that corporate reputation is unable to mitigate the negative price reaction of SEOs in Hong Kong, although it appears to complement underwriter reputation in doing so. In contrast to the main body of research, we also find that offers underwritten by reputable underwriters are associated with more negative abnormal returns on announcement.